The Role of Fourth Industrial Revolution on Small and Medium Size Enterprises in South Africa - Paul Saah; Charles Mbohwa (Research Synergy Foundation, 2025)
The Fourth Industrial Revolution (4IR) offers both transformative opportunities and significant challenges for Small- and Medium-Sized Enterprises (SMEs) in South Africa. The purpose of this study is to examine how 4IR technologies, such as robotics, the Internet of Things, and artificial intelligence (AI), affect the development and performance of SMEs in South Africa. With the use of a quantitative research methodology, this study meticulously investigates the connection between business outcomes and SME adaptation to 4IR. Using a descriptive single cross-sectional design and a nonprobability convenience sample technique, 50 SME owners and managers from the Eastern Cape province of South Africa were chosen to represent the entire nation. Version 27.0 of the Statistical Package for the Social Sciences (SPSS) was used to assess the collected information. The findings reveal a significant positive association between perceived business growth and SME adoption of 4IR technologies. Most businesses experienced improved operational efficiency and competitiveness after just a year of adaptation. However, opinions on 4IR adoption are greatly influenced by the characteristics of small enterprises, including their industry and location. Small business enterprises in more developed industries and urbanized locations are more likely to use 4IR technologies than SMEs in traditional or rural sectors, where issues like low levels of digital literacy, inadequate digital infrastructure and restricted access to finance still exist. However, all SMEs in South Africa must ultimately have fair access to 4IR technologies to promote long-term sustainability, competitiveness, and socioeconomic growth in the global digital economy.